Scabiosa atropurpurea Pincushion Flower, Sweet Scabiosa - Edward Gilman (EDIS, 2007)
This document provides an overview of Scabiosa atropurpurea, commonly known as Pincushion Flower or Sweet Scabiosa. It describes the plant as an annual that typically grows to a height of 1 to 3 feet with a spread of 1 to 2 feet. The plant has an upright habit and medium texture, with most leaves emerging from the soil. The flowers are deep pink and appear during the warm months, adding a showy element to gardens. Pincushion Flower thrives in full sun and can grow in a variety of soil types, including acidic, sandy, loamy, and clay soils. The document also includes information on planting times, spacing, and general care, noting that the plant has no major pest or disease issues. Original publication date October, 1999.